Sesame Street. Abby in Wonderland [videorecording (DVD)] - Carroll, Lewis, 1832-1898 (Genius Products : Distributed by Genius Entertainment, 2008)
Elmo the Red Rabbit is late, late, late, and has rushed away with Abby's wand in his back pocket. Abby must follow him down the rabbit hole and into Wonderland in order to get it back. She is hoping the Counterpillar or Rose-ita the Rose will help her. She will have to turn to Grover the Mad Hatter or Cheshire Cookie Cat for sound advice. Abby's adventures in Wonderland lead her right into the garden of Oscar, the Grouch of Hearts, who just so happens to have her wand. Now, she must beat him at his own game to get the wand back.